Partial hepatectomy due to trabecular hepatocellular carcinoma: Case report - Fernandes, Wallace da Silva; Fernandes, Jessica Batista; Barros, Beatriz Aparecida Correia de; Rosa, Bruna Zoz; Zambonini, Nathalia Melissa Hitos; Iashima, Camila Mika (Pubvet, 2023)
In small animal oncological routine, liver neoplasms are of low frequency, being separated into metastatic, malignant and benign. Hepatocellular carcinoma is the most common among cases of primary liver cancer, and its treatment can be carried out in different ways (conservative or surgical), with resection through hepatectomy being the recommended treatment that offers best results. This work aims to report a case of HCC in an 11-year-old dog who underwent surgical intervention of partial hepatectomy of two lobes, and had satisfactory results from the treatment.